“The Teacher Does Not Explain in Class”: An Exploration of the Drivers of Private Tutoring in Egypt - Maia Sieverding; Caroline Krafft; Asmaa Elbadawy (Global Labor Organization (GLO), 2017)
Widespread reliance on private tutoring has raised concerns over the hidden costs of Egypt's “free” education system. This paper examines the drivers of tutoring at different levels of education, using nationally representative survey data as well as qualitative data on youth experiences in public, private, and religious schools. Our findings indicate that the drivers of tutoring are multiple and vary by schooling level. Structured around high-stakes exams, the Egyptian education system has fostered the growth of a diverse tutoring market. In general secondary school, tutoring has become a social expectation that leads teachers and students to shirk in school to devote more attention to tutoring. In basic education, teacher pressure is a major motivation for public school students to take tutoring. In order to reduce the prevalence of tutoring and ensure greater equality in education, there is an urgent need to test mechanisms for ensuring accountability in schools. ****** Please cite the published version: Maia Sieverding, Caroline Krafft, and Asmaa Elbadawy. 2019. “An Exploration of the Drivers of Private Tutoring in Egypt.” Comparative Education Review 63(4): 562-590. doi:10.1086/705383 - available online at: https://www.journals.uchicago.edu/doi/full/10.1086/705383 ******
Additional information: Please cite the published version: Maia Sieverding, Caroline Krafft, and Asmaa Elbadawy. 2019. “An Exploration of the Drivers of Private Tutoring in Egypt.” Comparative Education Review 63(4): 562-590. doi:10.1086/705383 - available online at: https://www.journals.uchicago.edu/doi/full/10.1086/705383
Keywords: I21; I22; I24; N35; 330; Private tutoring; educational supplements; school quality; Egypt